Apotheosis Freemansonry Dalam The Lost Symbol - deni junaedi (Ars: Jurnal Seni Rupa dan Desain, 2010)
In the latest novel, The Lost Symbol, Dan Brown explains about “apotheosis”: “Human became God” or “Divinized Man”. Like in older novels, Brown uses art masterpieces to support his ideas, now explores Brumidi’swork, The Apotheosis of  Washington. He writes that apotheosis is in accordance with Bible, Koran, Bhagavad Gita, and others holy books; actually, there is no apotheosis concept in Koran. The world of  Freemasonry can not be separated with his novels.Keywords: The Apotheosis of  Washington, Constantino Brumidi,Freemasonry, The Lost Symbol.